Transforming Automobile Assembly Experience in Automation and Work Organization - Shimokawa, Kōichi 1930-; Jürgens, Ulrich 1943-; Fujimoto, Takahiro 1955- (Springer Berlin Heidelberg, 1997)
For leading the car-makers of the world the early 1990s brought significant changes, both in effectivity and profits. Formerly leading companies had to face consequences no one had expected. What are the results of the revolution in work organization and assembly automation? Scientists involved in those reports published in the early 1990s now gathered to evaluate the changes in worlds car-making industries. In this publication the reader will learn about todays concepts in automation and organization of produktion, in Japan, America and Europe. Five years later - how did the car-makers deal with the situation?
Keywords: Engineering; Engineering Economics, Organization, Logistics, Marketing; Control, Robotics, Mechatronics; Organization; R & D/Technology Policy; Planning; Control engineering; Robotics; Mechatronics; Engineering economics; Engineering economy; Economic policy; Montage; Arbeitsorganisation; Kraftfahrzeugindustrie; Automation